Aktivitas Enzim Peroksidase dan Kadar Klorofil pada Daun Angsana (Pterocarpus indicus) sebagai Peneduh Jalan yang terpapar Timbal - Anjar Astuti Ferdhiani; Sri Lestari; Elly Proklamasiningsih (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
One of emissions in the air that’s harmful to human  health is lead ( Pb ). The negative effects caused  by lead  and then required solutions for reducing the metal, its called phytoremediation. The Plant which acts as an agent of phytoremediation is Angsana (Pterocarpus indicus Willd.). Research to find out the lead content in Angsana’s leaf at four locations, knowing the influence of exposure to lead against the activity of an enzyme peroxydases and chlorophyll content in the Angsana’s leaf. The location for collection of samples conducted in four  location at Purwokerto (1) H.R Bunyamin, (2) Ovis Isdiman, (3) Gerilya, and (4) Dr. Soeharso. A method of the sample used purposive sampling.  Sample were analysed  using wet digestion method, then were analysed using Atomic Absorbance Spectrofotometer (AAS). The activity of peroxydases and levels of chlorophyll were analysed using spectrophotometer Uv Vis. Result showed that the lead content in Angsana’s leaf  is  0,1 – 0, 25 mg/L, the activity of peroxidases is  600- 1250 unit/g  and  chlorophyll content  is 9,0- 21,0 mg/L. The conclusion was no relations about chlorophyll content with levels of  lead content and the relations about activity of enzymes peroxydases and lead content is low . Content of  lead on Angsana’s leaf of  research has been done do not reach 1000 mg/L.